2017
DOI: 10.1039/c6tc04414j
|View full text |Cite
|
Sign up to set email alerts
|

Solution assembly MoS2nanopetals/GaAs n–n homotype heterojunction with ultrafast and low noise photoresponse using graphene as carrier collector

Abstract: A MoS2 nanopetal/GaAs homotype heterojunction with ultrafast and low noise photoresponse was solution assembled using graphene as the carrier collector.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 51 publications
2
33
0
Order By: Relevance
“…Quantification of the photodetector response to various light intensities is an important experiment for determining the photodetection performance of a heterojunction 38 , so we measured the current vs. bias voltage (logI-V) characteristics of the photodetector with respect to different light intensities ranging from the dark to 39.3 mW/cm 2 . Clearly, the photocurrent increased with increasing light intensity under reverse bias, resulting in reduced rectifying ratios (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Quantification of the photodetector response to various light intensities is an important experiment for determining the photodetection performance of a heterojunction 38 , so we measured the current vs. bias voltage (logI-V) characteristics of the photodetector with respect to different light intensities ranging from the dark to 39.3 mW/cm 2 . Clearly, the photocurrent increased with increasing light intensity under reverse bias, resulting in reduced rectifying ratios (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Emerging as a new class of artificial nanomaterials with fascinating physical properties, van der Waals (vdW) heterostructures can be achieved by integrating different 2D crystals. A large variety of 2D vdW heterostructures have already been employed to create high‐performance photovoltaic cells, field effect transistors, barristors, inverters, and memory devices . 2D layered‐material‐based heterostructures possess several unique advantages for applications in photodetectors.…”
Section: P–n‐junction‐based Photodetectorsmentioning
confidence: 99%
“…In contrast to the p–n junction, there are different band alignments in the n–n homotype heterojunction such that depletion and accumulation regions are created on opposite sides of the interface at thermal equilibrium, leading to majority carrier transport and enhancing the photoresponse speed of the device. In light of this, Jiang et al reported the solution assembly of a 2D MoS 2 nanopetal/GaAs n–n homotype junction with graphene as the carrier collector . The fabricated devices exhibited excellent photoresponse characteristics, including a high detectivity of up to 2.28 × 10 11 Jones at zero bias and a very fast response speed (rise and decay times of 1.87 and 3.53 µs) with an extended photoresponse range (400–1300 nm).…”
Section: P–n‐junction‐based Photodetectorsmentioning
confidence: 99%
“…In this case, the redox abilities of each component were not changed very much, unlike in p-n type junctions. 20,21 As a result, while maintaining the greater transition tendency of the charges between Bi 2 WO 6 and N-SrTiO 3 , the reductive ability of N-SrTiO 3 did not obviously decrease. The same case is observed for the oxidative performance of Bi 2 WO 6 .…”
Section: +mentioning
confidence: 94%
“…Unfortunately, the oxidative potentials (and/or reductive potentials) are bound to increase (and/or decrease) to establish a thermodynamic equilibrium with the same Fermi level of the semiconductors at the interface. 20,21 Thereby, at present, uniting a broad spectrum of redox capabilities, visible light response, and recycling stability for composite fabrication is a still crucial challenge.…”
Section: 12mentioning
confidence: 99%